Digital technology use in schizophrenia: a systematic review - Lapa, Ana Francisca Casinhas Coutinho (2022)
The use of digital technologies has been increasing among people with schizophenia spectrum disorder and it has been widely considered in diferente types of interventions. The fast development of technologies increases the need for confirming their feasibility, effectiveness, and efficacy. This study to review and synthesize the diferente types of digital tools and technologies used to treat people with schizophrenia and other conditions of the respective spectrum, besides its feasibility and acceptability. Following the PRISMA guidelines, a search was conducted on 1 March 2021 on several databases with 71 articles retrieved for the title and abstract screening. The inclusion criteria were applied. A total of six studies were included and the principal targets of the inerventions were motivational deficits (n=2), auditory verbal hallucinations (n=2), and cognitive symptoms (n=2). The acceptability and feasibility of digital technologies were confirmed, although their exact efficacy is still nuclear. Future studies need to consider increasing the size of the samples and create longer interventions to empower the evidence and allow the generalization of the results to enhance the efficacy of these interventions.